The Relationship Between Stress, Depression, and Suicidal Ideation among Adolescents in Gresik Regency - Widiyawati, Wiwik; Musfara, Deah Dwi (Journal Of Nursing Practice, 2026)
Background: Mental health disorders have become a serious concern due to their wide-ranging impacts, including the rising incidence of suicide. Suicide is an intentional act to end one’s life, influenced by both internal factors such as psychological and biological conditions, and external factors such as economy, environment, and technology. Adolescents and young adults represent vulnerable groups prone to stress and depression triggered by academic and social demands. When left unaddressed, these conditions may lead to the emergence of suicidal ideation. This situation underscores the need for mental health awareness and early prevention efforts among adolescents and young adults. Purpose: This study aimed to determine the relationship between stress and depression with suicidal ideation among adolescents in one of the districts of Gresik Regency. Methods: This study employed quantitative cross-sectional design. Data was collected using the Depression Anxiety Stress Scale (DASS-42) to assess stress and depression levels, and the Mini Plus 5.0.0 Questionnaire to measure suicidal idea. The study population consisted of 462 adolescents, with 215 respondents selected through simple random sampling. Ethical approval was obtained under No. 005/KET/II.3.UMG/KEP/A/2024. Data was analyzed using the Spearman Rank correlation test. Results: The correlation analysis between stress and suicidal ideation yielded a significance value of 0.01 (r=0.358, p-value < 0.05). Similarly, the correlation between depression and suicidal ideation also showed a significant value of 0.01 (r= 0.376, p-value < 0.05). Conclusion: The findings indicate that both stress and depression are significantly correlated with suicidal ideation among adolescents in Gresik Regency. Mental health problems, particularly stress and depression, can severely affect daily functioning among adolescents and young adults, leading to discomfort and vulnerability to suicidal thoughts due to inadequate coping mechanisms and environmental support.